Memaknai Realitas Dunia Maya: Kajian Dramaturgi dalam Film Semu - Zulfikar (Journal of Religion and Film, 2023)
This article attempts to look at the acute phenomenon of the social media generation with its activities and images in cyberspace. The film entitled "Semu" as a short film is able to depict the self-image of a teenager on social media nicely. A common social context in modern times where many people are accustomed to using smartphones and social media as part of their daily routine. On the other hand, the film Semu depicts that existence on social media is often important for individuals who want to portray a different image of themselves than they really are. This article finds that content and activities on social media are the main elements in shaping the online existence of a person or entity on platforms such as Facebook, Twitter, Instagram and other media. So falsehood on social media is a phenomenon where individuals or entities present information, images or identities that are inaccurate or do not correspond to reality via social media platforms. In this context, dramaturgy refers to theoretical analysis used in theater and performance studies to understand and dismantle false identities in cyberspace. The impact is that the public does not trust someone's activities on social media. Photos and videos can easily be used to manipulate netizens, their dismantling results in distrust of the images and content that someone continues to produce.